Deep Waters - Larry, H. I; Illustrated by Oswald, Ash (Australia Hardie Grant Egmont Victoria, 2006)
Zac power's next mission is in one of the deepest oceans in the world. Even GIB's subs can't handle the depth. But the enemy has invented a new sub that can dive deeper that ever before. Can Zac find the enemy, and protect the top-secret information stored on the seabed?
Include Illustration
Keywords: Submersibles -- Spy stories -- Submarine combat